416 The impact of Obstructive Sleep Apnea severity on age-related comorbities: a population-based study. (3rd May 2021) - Silva, Mayra; Poyares, Dalva; Oliveira, Luciana; Andersen, Monica; Tufik, Sergio; Piovesan, Ronaldo
Abstract: Introduction: Although age per se has been considered a risk factor for OSA, evidence suggest OSA in older adults may be less severe and OSA diagnostic criteria might be adjusted for this age group. Concurrently, it is likely the late-onset OSA is a distinct phenotype having different pathophysiological mechanisms, as well as clinical manifestations and consequences. We sought to investigate the clinical consequences of OSA severity in older adults from a representative sample of the older population living in the São Paulo city. Methods: From the baseline survey including 1042 participants in 2007, 715 were reassessed in 2016 completing full in-lab PSG, health-related questionnaires, blood tests, and blood pressure measurements. Individuals > 60 y.o. (n=199) of both genders were included in the analysis. Participants were stratified according to OSA presence and severity in 3 groups G1 (non and mild OSA n=83); G2 (moderate OSA n=56); G3 (severe OSA n=60). General Linear Model (GLM) tests and Chi-square were carried out. Results: Participants mean age was 70.02±7.31 and mean body mass index (BMI) 28.61±5.39, 40.71% of men. The only comorbidity associated with OSA severity was arterial hypertension occurring in 61.7% of G3, 46.4% of G4 and 41% of G1 (p=0.04). Severe OSA participants were more likely to use a higher (>2/day) number of medications (p=0.03). Finally, out of all blood tests only cortisol was significantly higher in severe OSA group (p<0.001) Conclusion: Severe OSA in older individuals of the general population is not associated with metabolic conditions, such as diabetes, but it was associated with hypertension. Severe OSA may be a stressful condition, since it was associated with higher cortisol in this population. Support (if any): Associaçao Fundo Incentivo a Pesquisa (AFIP)